1919
DOI: 10.1001/jama.1919.02610390032009
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Diseases of the Gallbladder and Biliary Ducts

Abstract: of the Rockefeller Institute which carried at the end this footnote :In experiments with magnesium sulphate I observed that the local application of a 25 per cent, solution of that salt on the mucosa [of the duodenum] causes a completely local relaxation of the intestinal wall. It does not exert such an effect when the salt is administered by the mouth, that is, when it has to pass through the stomach before it reaches the intestines. The duodenal tube, however, apparently has reached an efficient practical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0
2

Year Published

1922
1922
1976
1976

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…The very potent effect of intraduodenal magnesium sulphate in causing discharge of bile into the duodenum (Lyon, 1919;Matsuo, 1924;Simon, 1927;Boyden, 1928;Boyden and Birch, 1930;Ivy, et al, 1933;Bergh and Layne, 1942;Necheles and Kozoll, 1942;Boyden et al, 1943) has been confirmed by the present study, which has shown that infusion of magnesium sulphate into the duodenum elicits contraction of the gallbladder which is as great as that evoked by the combination of exogenous hormones in the dosage used in the present study. When administsred together with the exogenous hormones, the duodenal infusion of magnesium sulphate augmented the contraction of the gallbladder, compared with the response to the exogenous hormones alone.…”
Section: Discussionsupporting
confidence: 78%
“…The very potent effect of intraduodenal magnesium sulphate in causing discharge of bile into the duodenum (Lyon, 1919;Matsuo, 1924;Simon, 1927;Boyden, 1928;Boyden and Birch, 1930;Ivy, et al, 1933;Bergh and Layne, 1942;Necheles and Kozoll, 1942;Boyden et al, 1943) has been confirmed by the present study, which has shown that infusion of magnesium sulphate into the duodenum elicits contraction of the gallbladder which is as great as that evoked by the combination of exogenous hormones in the dosage used in the present study. When administsred together with the exogenous hormones, the duodenal infusion of magnesium sulphate augmented the contraction of the gallbladder, compared with the response to the exogenous hormones alone.…”
Section: Discussionsupporting
confidence: 78%
“…
It has been long known that magnesium sulphate given orally or by intraduodcnal instillation produces in man a contraction of the gallbladder and after a short spasm a relaxation of the Oddi's sphinc ter.Since Meltzer (1917) and Lyon (1919Lyon ( , 1923 found th at magnesium sulphate can evacuate the gallbladder, very num erous authors have confirmed such a result (reviewed by Crema, 1965).Nevertheless the mechanism of action of M gS04 introduced in the upper part of the intestine is still not clear. Two are the main hypothe ses in order to explain the contraction of the gallbladder and the relaxation of the Oddi's sphincter: (i) a nervous reflex arising from the duodenum (Pavel, 1959): (ii) a liberation of a hormonal m ediator.
…”
mentioning
confidence: 98%
“…Magnesium sulphate has previously been shown to cause an increase in colonic motor activity (Davidson, Sleisenger, Almy, and Levine, 1956), but it is difficult to be certain about its mechanism of action. It is a powerful stimulus for the release of cholecystokinin from small intestinal mucosa, as was originally shown indirectly by studies of gallbladder contraction (Lyon, 1919;Boyden and Birch, 1930;Boyden et al, 1943) and more recently confirmed by direct radioimmunoassay measurement of serum levels of cholecystokinin in normal subjects after oral MgSO4 Harvey, Grayburn, Jennings, and Hartog, 1974). Injection of this hormone results in an increase in both small intestinal (Adlercreutz, Pettersson, Adlercreutz, Gribbe, and Wegelius, 1960;Dahlgren, 1966;Parker and Bene-ventano, 1970) and colonic (Grossi et al, 1966;Dinoso et al, 1972;) motor activity.…”
Section: Discussionmentioning
confidence: 88%
“…Received for publication 6 September 1973. 983 related pain of the type described by Connell et al (1965), and four of eight such patients developed a typical attack of their usual pain after cholecystokinin, at the same time as markedly increased colonic motor activity was seen. In an attempt to ascertain whether endogenous CCK has a similar action, we have examined the effect on colonic motility of oral magnesium sulphate (MgSO,), a substance which is a powerful stimulus to endogenous cholecystokinin release (Lyon, 1919;Boyden and Birch, 1930;Boyden, Bergh, and Layne, 1943;Harvey, Dowsett, Hartog, and Read, 1973).…”
mentioning
confidence: 99%